Effect of copolymerizing fluorine‐bearing monomers on the relationship among internal structure, gas permeability, and transparency in copolymer networks composed of methacrylates and siloxane macromers. Issue 1 (27th April 2012) - Yokota, Mitsuru; Ajiro, Hiroharu; Akashi, Mitsuru
Abstract To clarify the effect of the type of acrylic monomer and the molecular weight (Mn) of polydimethylsiloxane (PDMS) on the relationship among the internal structure, oxygen permeability coefficient [P(O2)] and transparency, crosslinked copolymers were prepared with two different acrylic monomers : methyl methacrylate (MMA) and trifluoroethyl methacrylate (TFEMA). PDMS macromers with Mn of 1700, 3300, 4700, and 7800 g/mol were used. DSC measurements suggested that all constituent phases were insoluble with each other. The Mn of PDMS affected both the light transmittance and P(O2). The relationship between the Mn and P(O2) over the low Mn range (1700 and 3300 g/mol), and the calculated PDMS domain size ratio, were found to support the [Mn]2/3 rule into the crosslinked copolymer. Furthermore, a 3300 g/mol Mn copolymer became transparent when the amount of PDMS was greater than PMMA. In addition, copolymerization with TFEMA drastically affected those properties, and this effect was much greater than the effect of the PDMS Mn. To clarify the mechanism of P(O2) improvement induced by TFEMA copolymerization, calculations on the relationship among the P(O2), PDMS volume fraction, and morphology model were performed, and some properties such as solubility parameters should play important roles. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2012